Respuesta :
Answer:
[tex]f^{(0)}(0)} = 4 \\\\\ f^{(1)}(0) = -3 \\\\\f^{(2)}(0) = 4 \\\ \\f^{(3)}(0) = 4*3! = 24[/tex]
Step-by-step explanation:
Remember that in general the taylor series of a function [tex]f[/tex] are given by
[tex]f(x) = \sum_{n=0}^{\infty} \frac{f^{(n)}(0)}{n!}x^n = \frac{f^{0}(0)}{0!}+\frac{f^{(1)}(0)}{1!} x+ \frac{f^{(2)}(0)}{2!} x^2 + \frac{f^{(3)}(0)}{3!} x^3 + ......[/tex]
therefore
[tex]\frac{f^{(0)}(0)}{0!} = 4 \\\frac{f^{(1)}(0)}{1!} = -3 \\\\\frac{f^{(2)}(0)}{2!} = 1\\\frac{f^{(3)}(0)}{3!} = 4[/tex]
and then
[tex]f^{(0)}(0)} = 4 \\\\\ f^{(1)}(0) = -3 \\\\\ f^{(2)}(0) = 4 \\\ \\f^{(3)}(0) = 4*3! = 24[/tex]
Comparing with the general Taylor expansion, we will see that the coefficients are:
- f(0) = 4
- f'(0) = -3
- f''(0) = 2!*5 = 10
- f'''(0) = 3!*4 = 3*2*4 = 24
How to work with a Taylor polyomial?
For a function f(x), the Taylor polynomial around x = 0 is:
T(x) = f(0) + f'(0)*(x) + (1/2!)*f''(0)*x^2 + (1/3!)*f'''(0)*x^3 + ...
In this case, we have:
T(x) = 4 − 3x + 5*x^2 + 4*x^3
Comparing the correspondent coefficients with the ones in the general expansion, we can see that:
- f(0) = 4
- f'(0) = -3
- f''(0) = 2!*5 = 10
- f'''(0) = 3!*4 = 3*2*4 = 24
If you want to learn more about Taylor expansions, you can read:
https://brainly.com/question/9211177